Anthropometric, physiological and maturational characteristics in selected elite and non-elite male adolescent basketball players - Torres-Unda, J.; Zarrazquin, I.; Gil, J.; Ruiz, F.; Irazusta, A.; Kortajarena, M.; Seco, J.; Irazusta, J. (Journal of Sports Sciences, 2013)
We investigated the anthropometric, physiological and maturation characteristics of young players (13-14 years old) associated with being successful in basketball. Body parameters were measured (stature, total body mass, skinfolds and lengths) and physiological capacities were assessed by endurance, sprint (20 m), jump and dribbling tests. Chronological age (CA) was recorded and maturity estimated using predicted age at peak height velocity (APHV). Anthropometric analysis indicated that elite players were taller, heavier and had a higher percentage of muscle. Further, physiological testing showed that these elite players perform better in jump, endurance, speed and agility tests (especially in the agility and ball tests). In addition, these skills are correlated with point average during the regular season. More basketball players born in the first semester of the year are selected and there is a predominance of early-maturing boys among those selected for the elite team. Those who are more mature have advantages in anthropometric characteristics and physiological test results. In conclusion, around puberty, physical and physiological parameters associated with maturity and CA are important in determining the success of basketball players. These findings should be taken into account by trainers and coaches, to avoid artificial bias in their selection choices.